The osseous industry from Manot Cave (Western Galilee, Israel): Technical and conceptual behaviours of bone and antler exploitation in the Levantine Aurignacian. (1st June 2016) - Tejero, José-Miguel; Yeshurun, Reuven; Barzilai, Omry; Goder-Goldberger, Mae; Hershkovitz, Israel; Lavi, Ron; Schneller-Pels, Nehora; Marder, Ofer
Abstract: The Early Upper Palaeolithic in the Levant plays an important role in understanding the emergence, dispersal, and adaptations of the first Anatomically Modern Human (AMH) populations in the Levant and Europe. The technical exploitation of osseous raw materials, represented by the new concepts applied to the antler working, is recognized as one of several innovations that occur both in the Levant and in Europe during this time. Here we present preliminary results of a technological analysis conducted on the Aurignacian bone and antler industry from the Early Upper Palaeolithic layers of Manot Cave, Israel. The industry displays several similarities with its European counterpart such as the choice of bone for making "domestic" tools (recurrent morpho-types like awls) while antler was used predominantly for hunting equipment (projectile points). The complex technical exploitation of antler, almost exclusively devoted to making hunting weapons, constitutes a major feature both in the European Early Aurignacian and in the Levantine Aurignacian. Nevertheless, while simple-based antler points are common in the Levantine Aurignacian, split-based antler points, characteristic of the European Early Aurignacian are only anecdotally documented in the Levant. Unique to the Levantine industry is the common exploitation of fallow deer antler. While some of these particularities seem to be related to the different ecological niches exploited, others, such as the different type of hunting weapons, need to be assessed in light of different cultural contexts.